Is there a difference in the oxidative stress levels between type 2 diabetic individuals with and without periodontitis? Systematic review: Systematic review - Lobão, Walder Jansen de Mello; Menezes, Claudia Callegaro de; Marañón-Vásquez Guido Artemio; Masterson, Daniele; Maia, Lucianne Cople; Barros, Maria Cynésia Medeiros de; Silva-Boghossian, Carina Maciel; Sansone, Carmelo (Brazilian Dental Science, 2024)
Objective: The authors’ aim in this systematic review was to verify the scientific evidence for difference of oxidative stress biomarkers in individuals with type 2 diabetes mellitus with and without periodontitis. Material and Methods: Observational studies, baseline data of prospective and interventional studies were searched on the following databases: Virtual Health Library, Web of Science, PubMed, Embase, Scopus, Cochrane Library, Opengrey and Google Scholar. The electronic search was performed in June 01, 2020 until May 17, 2024 with alerts until June 01, 2024. The quality assessment and the certainty of the evidence of the included studies were evaluated through Fowkes and Fulton’s checklist and GRADEpro Guideline Development Tool. Results: Of 988 relevant articles, the authors included 9 studies for the final analysis. Among those studies, 4 cross-sectional, 3 case-control, and 2 interventional studies were included. The analysis of non-randomized clinical trials properly reported most of the criteria analyzed in Summary questions (Bias, Confounding and Chance) as present in 3 studies. In six studies confounding factors were no detected. Due to the variation in the study results and clinical/ methodological heterogeneity, a meta-analysis was not appropriate. The studies reported high concentrations of oxidizing agents and low antioxidants levels in individuals with type 2 diabetes mellitus and periodontitis when compared to with no periodontitis. Conclusion: Considering the few studies found, the methodological flaws, few markers studied and absence homogeneity in the evaluation of redox balance markers, as well as, the very low certainty of the evidence among included studies, it was not possible to determine whether there are or not differences in the oxidative stress levels in individuals with type 2 diabetes with and without periodontitis, and therefore, further prospective observational and interventional studies are recommended. KEYWORDS Diabetes mellitus non-insulin dependent; Periodontitis; Periodontal diseases; Oxidative stress; Antioxidants; Free radicals.